Advanced manufacturing and automation : selected, peer reviewed papers from the 4th International Workshop of Advanced Manufacturing and Automation (IWAMA 2014), October 27-28, 2014, Shanghai, China - Wang, Kesheng; Strandhagen, Jan Ola; Tu, Dawei (Advanced materials research, 2014)
Collection of selected, peer reviewed papers from the 4th International Workshop of Advanced Manufacturing and Automation (IWAMA 2014), October 27-28, 2014, Shanghai, China. The 97 papers are grouped as follows: Chapter 1: Mechanisms and Machine of Manufacturing Systems, Chapter 2: Advanced Manufacturing Technologies, Chapter 3: Measurements, Monitoring and Analysis of Manufacturing Systems, Chapter 4: Mechatronics, Robotics and Control, Chapter 5: Intelligent Manufacturing Systems, Chapter 6: Production, Logistics and Supply Chain Management. Keyword: Intelligent Manufacturing Systems; Advanced Manufacturing Systems; Logistics and Supply Chain Management; Production Management; Robotics and Automation; Intelligent monitoring and Maintenance; Renewable Energy and Environment Editors Wang, Strandhagen, and Tu present students, academics, researchers, and manufacturing professionals with a selection of peer-reviewed papers drawn from materials presented at the fourth International Workshop of Advanced Manufacturing and Automation, held in October, 2014 in Shanghai, China. The materials presented in the collection are organized in six chapters, covering mechanisms and machines of manufacturing systems, advanced manufacturing technologies, measurements, monitoring, and analysis of manufacturing systems, mechatronics, robotics, and control, intelligent manufacturing systems, and production, logistics, and supply chain management. Kesheng Wang is a faculty member of the Norwegian University of Science and Technology. Jan Ola Strandhagen is a research director at SRK NORMAN at SINTEF. Dawei Tu, is a faculty member of Shanghai University, China. -- Logistics-- Mechanical engineering-- Robotics.